Mechanical and microstructural characterization of rice husk ash and Al2O3 nanoparticles modified cement concrete. (20th September 2020) - Meddah, M.S.; Praveenkumar, T.R.; Vijayalakshmi, M.M.; Manigandan, S.; Arunachalam, R.
Highlights: Effect of Al2 O3 nanoparticles on mechanical and durability properties studied. Al2 O3 nanoparticles improve particle packing density of concrete. Al2 O3 nanoparticles densify its microstructure. Blends of RHA & Al2 O3 -Nanoparticles improved mechanical and durability properties. 3% Al2 O3 nanoparticles was found to be the optimum replacement level. Abstract: Waste and by-product materials both in their macro and micro-sizes are nowadays gaining more importance and consideration for their use as a partial substitute of the virgin concrete s constituents. Nanoparticles have now also gained widespread recognition and used in various construction applications, especially cement-based materials. The present paper examines the impacts of a combination of Al2 O3 nanoparticles along with Rice Husk Ash (RHA) on both mechanical properties (Flexure, Splitting tensile and Compressive) strengths and durability properties, including resistance to hydrochloric acid attack and chloride permeation. RHA substituted Portland cement (PC) at a fixed amount of 10%, and Al2 O3 nanoparticles have been utilized as a partial substitution of PC at 1%, 2%, 3%, and 4%. Surface morphology and microstructure of modified cement concretes were assessed by means of the Scanning Electron Microscope (SEM). The results revealed that Al2 O3 nanoparticles have double effects as a filling material. As a reactive one, increasing contribution in the volume of calcium silicate hydrates (C-S-H) formed thereby increases the strengths and durability properties of concrete material. It has also been found that 3% content of Al2 O3 nanoparticles is the optimum content to substitute part of the cement leading to the greatest mechanical and durability properties enhancement. The combination of up to 3% Al2 O3 nanoparticles along with 10%RHA to design modified cement concretes with enhanced strength and durability performances have revealed to be efficient and productive for eco-friendly concrete material.